The effectiveness of mathematics learning with the ethnomatematics approach to understanding junior high school students’ concepts - Nurtriana, Nanda Ade Ilma; Nuryadi, Nuryadi (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This study aims to determine the effectiveness of mathematics learning using an ethnomathematics approach in improving students' conceptual understanding of quadrilaterals in grade VII at SMP Negeri 3 Godean. The research design was quasi-experimental with a one-sample pretest-posttest control group. Two classes were involved: VIIA as the control group and VIIC as the experimental group. The instruments used were pretest and posttest. The ethnomathematics approach linked geometric concepts to local culture, specifically the Joglo house in Yogyakarta. The results showed that the average posttest score of the experimental group increased by 15.19 points, indicating a significant improvement in conceptual understanding. In contrast, the control group, which used conventional teaching methods, showed less improvement. Based on these findings, it can be concluded that mathematics learning with an ethnomathematics approach is effective in enhancing students' understanding of quadrilaterals. This approach makes learning more relevant to local culture, making it more engaging and meaningful for students.